Transformation of Ecological Citizenship Based on Green Open Space: Civic Education, Social Construction, and Citizen Participation in the Management of Bandung City Green Open Space Parks - Julian Mauludi Fadhillah; Dasim Budimansyah; Leni Anggraeni (MASI Mandiri Edukasi, 2026)
Urban ecological crises demand a citizenship approach that goes beyond normative compliance and emphasizes citizens' ecological responsibility in public spaces. In Bandung City, the achievement of green open space (GOS) in 2020 reached only 12.25% of the total city area, far below the minimum requirement of 30%. This issue is not only structural but also cultural, as reflected in low citizen participation and the dominant perception of parks merely as recreational spaces. This article analyzes how Bandung City residents construct the functions of GOS parks and the role of Civic Education (PKn) in fostering ecological citizenship through citizen participation. The research employs a qualitative phenomenological approach, using field observation, in-depth interviews, and policy documentation. Data analysis was conducted through reduction, display, and verification. The research results indicate that citizens' social construction of GOS remains oriented toward social-recreational purposes and has not yet been fully internalized as an ecological obligation. The novelty of this research lies in conceptualizing GOS as a civic learning space that connects the social construction of public space with ecological citizenship within a Civic Education perspective. These findings strengthen the argument that strengthening Civic Education based on local GOS issues contributes significantly to the sustainability of city parks.